2007
DOI: 10.1007/s00256-006-0200-7
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent gossypiboma in the thigh

Abstract: Gossypiboma, an iatrogenic mass lesion caused by a retained surgical sponge is an extremely rare event following musculoskeletal procedures. This entity is therefore a very unusual experience and can create considerable confusion. Unsuspecting surgeons may thus be caught out by this unlikely presentation. We present our experience with a recurrent gossypiboma in the thigh occurring several years after surgical evacuation of a similar gossypiboma from the same anatomic location with interval resolution of sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Depending on the site of implantation, gossypiboma can mimic a variety of lesions including ovarian tumors and soft tissue neoplasms . In some cases, “local recurrence” occurred after surgical removal . Even though this is a benign lesion, it can lead to surgical site infection and sepsis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the site of implantation, gossypiboma can mimic a variety of lesions including ovarian tumors and soft tissue neoplasms . In some cases, “local recurrence” occurred after surgical removal . Even though this is a benign lesion, it can lead to surgical site infection and sepsis.…”
mentioning
confidence: 99%
“…7 In some cases, ''local recurrence'' occurred after surgical removal. 8 Even though this is a benign lesion, it can lead to surgical site infection and sepsis. The reported mortality rate ranges from 11 to 35%, 9 and longstanding gossypiboma has been reported in association with angiosarcoma.…”
mentioning
confidence: 99%
“…Gauze is recognized as the most frequently forgotten surgical material, accounting for up to 80% of reported cases (6,17). Reports of gossypibomas after orthopaedic procedures are relatively infrequent compared to abdominal surgeries accounting for only six percent of gossypiboma cases in the human medical field compared to 52% being found in the abdomen (6,17,(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported the initial diagnosis of an extraskeletal osteosarcoma in a dog (Miller et al, 2006) and a recurrent soft tissue neoplastic mass in the thigh (Puri et al, 2007) and a paraspinal abscess , in both these cases surgical swabs were found on surgical exploration.…”
Section: Veterinary Nursing Journalmentioning
confidence: 97%